Analisis Kebutuhan Media Google Sites Dalam Pembelajaran IPS Pada Siswa Kelas IV Sekolah Dasar - Diyana Hafizah; Budiansyah, Budiansyah; Maharani, Siti Dewi; Nurani, Dwi Cahaya; Susiloningsih, Esti (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2025)
This study aimed to analyze the need for developing Google Sites based learning media in Social Studies instruction, particularly for the topic Norms in Local Customs, for fourth grade elementary school students. The study employed a descriptive qualitative approach involving one fourth grade teacher and 15 students. Data were collected through classroom observations, in depth teacher interviews, and student needs questionnaires. Qualitative data were analyzed using the interactive model proposed by Miles and Huberman, while questionnaire data were analyzed using the Guttman Scale. The findings indicated that the learning media currently used were limited to PowerPoint presentations and static images, which were insufficient to optimally integrate multimodal elements and did not adequately support students’ independent learning. Classroom observations revealed that the learning process remained predominantly teacher centered and one directional. Interview results showed that teachers required instructional media capable of presenting local cultural visualizations in a contextual manner that was relevant to students’ lived experiences. Meanwhile, the questionnaire results demonstrated a very high level of student need for interactive, visual, and contextual digital learning media, with an average percentage of 96%. Based on these findings, it can be concluded that the development of Google Sites based learning media is highly necessary as a solution to bridge the abstract nature of Social Studies content with the learning needs of elementary school students. Google Sites has the potential to serve as a relevant instructional alternative, as it enables the integration of various learning resources within a single, flexible, and easily accessible platform.